Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Kober Mie Setan Soekarno-Hatta Malang - Arif Baihaqi; N. Rachma; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the effect of product quality and service quality partially on customer satisfaction Kober Mie Setan Malang. To determine the effect of product quality and service quality simultaneously on customer satisfaction Kober Mie Setan Malang. The population of this study is Kober Mie Malang customers, amounting to 5,600 while the sample in this study amounted to 98 consumers. Data analysis uses multiple linear regression analysis.The results showed that the effect of product quality and service quality partially had a significant effect on customer satisfaction Kober Mie Setan Malang. the influence of product quality and service quality significantly influence customer satisfaction Kober Mie Setan Malang. Keywords: product quality, service quality, customer satisfaction